2013
DOI: 10.1371/journal.pone.0030243
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 at 50x AI Attenuates the Decline in Paw Grip Endurance, but Not Disease Outcomes, in the G93A Mouse Model of ALS, and Is Toxic in Females

Abstract: BackgroundWe previously demonstrated that dietary vitamin D3 at 10x the adequate intake (AI) attenuates the decline in functional capacity in the G93A mouse model of ALS. We hypothesized that higher doses would elicit more robust changes in functional and disease outcomes.ObjectiveTo determine the effects of dietary vitamin D3 at 50xAI on functional outcomes (motor performance, paw grip endurance) and disease severity (clinical score), as well as disease onset, disease progression and lifespan in the transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
(59 reference statements)
2
22
1
4
Order By: Relevance
“…Furthermore, we found that when corrected for disease severity HiD mice had 5% greater ATM versus AI mice, and HiD males had 81% greater MP versus AI males. Indeed, we observed similar functional and disease outcomes in a much larger, higher dose follow-up study using the same mouse model [20]. For humans, this would indicate that vitamin D 3 supplementation far above the adequate intake may improve ambulation at the same stage of disease versus no supplementation.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, we found that when corrected for disease severity HiD mice had 5% greater ATM versus AI mice, and HiD males had 81% greater MP versus AI males. Indeed, we observed similar functional and disease outcomes in a much larger, higher dose follow-up study using the same mouse model [20]. For humans, this would indicate that vitamin D 3 supplementation far above the adequate intake may improve ambulation at the same stage of disease versus no supplementation.…”
Section: Discussionsupporting
confidence: 69%
“…20 20 Fat (%) 7 7 Vitamin D 3 (IU/g) 1 a 10 a,b Calcium (%) 0.5 c 0.5 c Vitamin mix V10037 (mg/g) 10 10 Mineral mix S100022G (mg/g) 35 35 Diets provided by Research Diets (based on AIN-93G; New Brunswick, NJ; AI product # D10012G; HiD product # D08080101). a included in vitamin mix V10037.…”
Section: Food Intake and Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that vitamin D could ameliorate pathological mechanisms [15] and that supplementation could slow the disease course [12,16]. On the other hand, reports from a high copy SOD1 G93A-mutated transgenic mouse model of ALS suggest that administration of vitamin D could alter dopaminergic activity in the brain [16], which may be toxic to female pups [14] and, when deficient, may delay onset and attenuate early disease severity [17]. In one study, vitamin D supplementation in rodents did not produce beneficial effects on age of onset or disease duration [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed vitamin D status in neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease (Buell et al, 2010;Gianforcaro and Hamadeh, 2012). Recent studies on the G93A transgenic mouse model of ALS showed improved functional outcome compared to control mice after supplementation of vitamin D Hamadeh, 2012, Solomon et al, 2011;Gianforcaro et al, 2013). Moreover, vitamin D applied on motoneurons cultured in vitro seems to potentiate the effects of glial-and brainderived neurotrophic growth factors, protecting cells from Fas-induced cell death (Camu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%